Sexual maturity, habitat and ecological aspects of the range expansive Isopod Sphaeroma venustissimum in Tunisian waters (Central Mediterranean Sea) - Ounifi Ben Amor, Khadija (Array, 2018)
A total of 4665 specimens of Sphaeroma venustissimum Monod, 1931 were collected between February 2012 and January 2013, in Tunis Southern Lagoon, a brackish area located in northern Tunisia. This species was mainly recorded in the Atlantic Ocean and recently extended its natural range toward the southern Mediterranean Sea. Biological and ecological traits were not available to date with special regard to its native and recipient habitat. S. venustissimum isopoda inhabits area below stones covered by biofouling and empty nests of barnacles. The species occursand reproduces in Tunis Southern Lagoon throughout the year with a peak in early spring and late summer. Males significantly outnumbered females during high reproductive activity period (May - July). The first gravid female was observed at 7 mm and the fecundity ranged between 6 and 17 eggs. Among the gravid females, a significant relationship was noted between the importance of brood versus total body length for all ovigerous female cohorts. The recruitment occurred throughout the year with a winter peak. S. venustissimum have established a sustainable population in Tunisia and have spread into the wild in its new host area.